Carotid intima-media thickness and subclinical left heart dysfunction in the general population. (July 2020) - Nakanishi, Koki; Daimon, Masao; Yoshida, Yuriko; Ishiwata, Jumpei; Sawada, Naoko; Hirokawa, Megumi; Kaneko, Hidehiro; Nakao, Tomoko; Mizuno, Yoshiko; Morita, Hiroyuki; Di Tullio, Marco R.; Homma, Shunichi; et al.
Abstract: Background and aims: Although carotid intima-media thickness (IMT) is an established marker of atherosclerosis and carries independent risk for cardiovascular disease, its possible association with subclinical cardiac dysfunction has not been extensively evaluated. Left ventricular global longitudinal strain (LVGLS) and peak left atrial longitudinal systolic strain (PALS) can detect subclinical left heart dysfunction. This study aimed to investigate the association between carotid IMT and subclinical left heart dysfunction in a sample of the general population without overt cardiac disease. Methods: We examined 1161 participants who underwent extensive cardiovascular examination. Ultrasonography of common carotid artery was performed for the measurement of maximal carotid IMT. LVGLS and PALS were assessed by 2-dimensional speckle-tracking echocardiography. Results: Mean age was 62 ± 12 years, and 56% were male. The prevalence of abnormal LVGLS (>-18.6%) and PALS (<31.4%) was greatest in the upper quartile of carotid IMT (both p < 0.001). In multivariable analyses, carotid IMT was associated with abnormal LVGLS (adjusted odds ratio = 1.33 per 1SD increase of IMT, p = 0.003) as well as PALS (adjusted odds ratio = 1.33 per 1SD increase of IMT, p = 0.005) independent of traditional cardiovascular risk factors, echocardiographic parameters including LV ejection fraction, LV mass index and diastolic dysfunction, and pertinent laboratory parameters. The independent association between carotid IMT and PALS persisted even after adjustment for LVGLS. Conclusions: Participants with increased IMT had significantly impaired LV and LA function in an unselected community-based cohort. This association may be involved in the higher incidence of cardiovascular disease in individuals with increased carotid IMT. Graphical abstract: Image 1 Highlights: The association between carotid intima-media thickness (IMT) and left heart strain was investigated in 1161 participants. The prevalence of abnormal left ventricle (LV)/left atrium (LA) strain was greatest in the upper quartile of IMT. Increased IMT was independently associated with decreased LV and LA strain. The association between IMT and LA strain was independent of LV morphology and function.